On Becoming 21st Century Reading Educators: “Are Teacher Educators and the Curriculum Critical Enough in Critical Reading Instruction?” - Mahayanti, Ni Wayan Surya; Suwastini, Ni Komang Arie; Riastini, Putu Nancy; Rachman, Dzul; Rajab, Abd (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Reading critically empowers students' learning for justice, equality and coherence in their lives and in society as a whole. Unfortunately, student teachers and faculty members continue to struggle with enhancing their critical reading and skills. Therefore, it is essential to conduct a formative assessment of critical reading instructors and the curriculum. This study identifies the lecturers' perceptions of the concept of a critical reading course and assesses whether the learning outcomes of critical reading meet the critical reading dimension and the heutagogy principle. Employing qualitative methods, a comprehensive understanding of the lecturers' understanding of critical reading and its implementation in the classroom was acquired. In this study, the sample consisted of four instructors of critical reading courses who were reqruited using purposive sampling technique. Data analysis was based on an inductive, constant comparative method through an initial reading of the interview transcripts and documents, apparent themes were identified and coded, and categories of language use were determined. It was discovered that they struggled to define the concepts of critical reading and had no specific strategies for teaching this course. Critical reading's primary objective is not empowerment. These results were supported by the analysis of the course's syllabus, which revealed that none of the social levels of critical reading proficiency were developed in this class. In addition, critical reading is viewed solely as a cognitive skill and has not yet reached the critical dimension. Thus, it is of the utmost importance to replace and revise learning outcomes.